(untitled) (City: History, Culture, Society, 2018)
The research of the defensive structures of the Kyiv-Pechersk Lavra includes many important aspects requiring serious architectural, archaeological and bibliographic research. Among of them the question of the stages of their construction and the evolution of the building. In the article is described assumption about the initial functional purpose of the premises of the South Tower, Onufriyivsky tower and Ivan Kashnikov tower, not only for the rifles firing during combat operations but also for the guard of residence. For the first time is presented the reconstruction of some sections of the monastery walls and the Kashnikov tower in the initial construction period.